Poly(epsilon-caprolactone) based polymer electrolytes and its application in flexible solid supercapacitors - Woo, H.J.; Arof, Abdul Kariem (2015)

(untitled)
Supercapacitors can be used as stand alone or complement batteries and solar cells to form hybrid systems that provide high power density and ultra fast charge-discharge rate. Flexible solid supercapacitor have recently been developed indicating tremendous opportunities with this new generation solid energy storage devices because it is thin, light weight, flexible, low maintenance, minimize leakage and easy sealing processes. In this work, proton-conducting polymer electrolytes based on poly (epsilon-caprolactone) (PCL) containing ammonium thiocyanate (NH4SCN), ethylene carbonate (EC) and succinonitril (SN) will be presented. The polymer membranes were prepared by solution casting. The potential of electrical double layer capacitors (EDLCs) fabricated from symmetry activated carbon electrodes and the PCL based films has been studied. The highest conducting samples show a room temperature ionic conductivity of 4.3 x 10-3 S cm-1. The fabricated EDLC cells were preliminary evaluated by cyclic voltammetry studies. The highest specific capacitance of EDLC cell is found to be 27.7 F g-1 at scan rate 10 mV s-1. Different cell designs will also be discussed.